Effects of Non-Uniform Channel Geometry on Double-Gate MOSFET Performance - Xu Huifang; Dai Yuehua; Zheng Changyong; Xu Jianbin; Yang Jin; Dai Guangzhen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A Double-gate (DG) MOSFET with non-uniform channel (NUC) geometry, that is, the silicon thickness of embedded in double-gate is varied linearly from drain to source, is proposed. To quantitatively assess the effects of the NUC geometry on electrical characteristics of DG MOSFETs, the short-channel effects (SCEs) and the on-state current are numerically calculated for the device with different non-uniform channel thickness, channel length and gate oxide thickness respectively. To the proposed structure, the SCEs are suppressed, the subthreshold swing becomes smaller and the on-state current is significantly improved when the thickness of silicon lied at source becomes thinner, showing better performances than the conventional DG MOSFETs.